Longitudinal relations of prematurity and fetal growth restrictions with hyperactivity/inattention and aggression/delinquency - Zumbach-Basu, Jelena; Rademacher, Annika; Koglin, Ute; Bender, Doris; Lösel, Friedrich (Pediatric Research, 2024)
Background: It is the aim of this study to analyze the longitudinal relationship between premature birth and low birth weight and the reciprocal influence between hyperactive/inattentive behavior and aggressive/delinquent behavior problems in children from early to late childhood. Methods: This study contains data from the German Erlangen-Nuremberg Development and Prevention Study. It applies prospective longitudinal path analyses on data obtained from postnatal pediatric assessments as well as later psychosocial behavior assessments by teachers and parents on N = 667 children, out of which n = 83 children (12.44%) were born preterm/small for gestational age. Results: The results show direct effects of birth complications at the beginning of preschool on hyperactivity/inattentiveness (teacher rating: ß = 0.28; p = 0.017; parent rating: ß = 0.32; p = 0.005), but not on aggression/delinquency (teacher rating: ß = 0.002; p = 0.427; parent rating: ß = 0.12; p = 0.324). Reciprocal effects between aggression/delinquency and hyperactivity/inattentiveness were stable at the end of elementary school, but not at the end of preschool across informants. Conclusion: Our results support a differentiated view on the potential development of behavior problems after birth complications and the demand for early prevention measures. Impact Statement: Our results extend to the existing body of research by providing insight into the longitudinal effects of prematurity and fetal growth restrictions on hyperactive and aggressive/delinquent behavioral problems throughout a rather long period of development in childhood. The results show direct effects of birth complications on the development of hyperactivity for boys, but not for girls across informants. No direct effects of birth complications on aggression/delinquency are found. Our findings speak against too simple views on behavioral consequences of birth complications and thus can relieve too anxious parents, however close monitoring of the behavioral development of respective children is indicated.
CRIS-Team Scopus Importer:2024-06-28